Optimization for the efficient recovery of poly(3-hydroxybutyrate) using the green solvent 1,3-dioxolane - Wongmoon, Chanakarn; Napathorn, Suchada Chanprateep (Frontiers in Bioengineering and Biotechnology, 2022)
A non-toxic and simple recovery process of biodegradable poly(3-hydroxybutyrate) (PHB) using the green solvent 1,3-dioxolane and water was successfully developed. In this study, the critical parameters have been optimized and scaled up the process platform for efficient recovery of PHB from 2 mL to 1000 mL. The physical parameters which included continuous shaking, ultrasonication, Soxhlet extractor, diluted 1,3-dioxolane, reused 1,3-dioxolane and cell rupture by steam explosion prior to solvent extraction were carefully investigated. The results showed that continuous shaking played the most important factor in recovery efficiency during the scale-up of the recovery process. The extraction process at 2 mL from dried cells at 80°C with 100 rpm of shaking speed for 5 h resulted in a recovery yield of 96.6 ± 0.1% with purity up to 99.1 ± 0.6%. The PHB extracted from wet cells under the same condition resulted in a recovery yield of 94.6 ± 4.8% and purity of 97.0 ± 0.1%. Notably, the PHB extracted from wet cells at room temperature with 150 rpm of shaking water bath for 36 h resulted in a recovery yield of 93.5 ± 0.7% and purity of 97.7 ± 1.3% and had an MW of 3.1105, MN of 2.7105, polydispersity index of 1.1. The direct scale-up process at 1000 mL showed comparable results in purity, recovery yield, molecular weight distribution, thermal properties, and mechanical properties. The PHB extraction from dried cells gave the highest purity of 99.3 ± 0.5% and recovery of 94.0 ± 0.3% whereas the PHB extraction from wet cells gave a purity of 90.3 ± 1.5% and recovery of 92.6 ± 1.0%. The novel recovery process showed its feasibility to be applied on an industrial scale.